Case Study on The Feasibility of The English Study Program at Politeknik Negeri Bengkalis and Industry Interest in Its Graduates. - Satria, Ari; Destianingsih, Arita (Politeknik Negeri Bengkalis, 2024)
This study aims to analyze the feasibility of the English Diploma Program at Bengkalis State Polytechnic andthe interest of the industry towards its graduates. The research idea stems from the phenomenon and issue of a significantdecline in student enrollment over the past five years. Data collection techniques include observation, in-depthinterviews, questionnaires, and documentation. The respondents for this research are students of the English DiplomaProgram, alumni, lecturers, leaders, and industry practitioners related to the research problem. Data analysis was carriedout using content analysis, which involves examining the collaboration of all collected data, interpreting it, drawingconclusions, verifying the facts found, and narrating the results. This research shows that the English Program atBengkalis State Polytechnic has adequate facilities, but improvements are needed in technology access and industryconnections. Students are generally satisfied with the quality of teaching and the relevance of the curriculum, althoughmore practical opportunities and stronger industry links are expected. Alumni find the graduates satisfactory, but there isa need to enhance soft skills, technological skills, and work experience. To face the challenges of modern industries,curriculum improvements, practical skills development, and industry collaboration are necessary. However, the interviewresults show that the majority of alumni agree that the English Diploma 3 Program should be discontinued to make wayfor the development of the Applied Bachelor's Degree (D4) Program.